European integration and EU eastward enlargement process in international trade: using a gravity approach for exploring bilateral trade flows - Tiiu Paas (European Regional Science Association (ERSA), 2002)
The paper is going to give an overview of the comparative evaluation of the Baltic Sea region countries (Sweden, Denmark, Finland, Norway, Germany, Russia, Poland, Estonia, Latvia and Lithuania) competitiveness based on various methodological approaches ranking countries according to their level of international competitiveness. The study mainly bases on the data of the United States Agency for International Development (USAID), Harvard Institute for International Development (HIID), International Institute for Management Development (IMD) and national and international statistical authorities. Factor analysis as a data reduction method is used in order to elaborate generalized indicators (factors) of a country's competitiveness level and to compare the factor analysis based rankings of the Baltic Sea region economies with the ranking results based on the other methodological approaches (HIID methodology for evaluation of the economies' in transition competitiveness, World Competitiveness Yearbook (WCY) methodology). According to the results of using factor analysis, the main generalized indicators that explain a country's competitiveness level are the size of economy and level of economic development, which explain more than 50% of variation of initial indicators of a country's macroeconomic environment. Other generalized indicators could be interpreted as the factors that characterize development of infrastructure and/or human resources, and also openness of economy. Based on the results of the study, it is possible to conclude that the Baltic Sea region countries have good competitive position among the leading world economies and the economies in transition. The countries around the Baltic Sea have historical and cultural traditions for developing trade relations and economic cooperation. The development of mutually beneficial economic co-operation between the capital abundant countries such as Germany and the Scandinavian countries and the transitional countries of the region, which provide the possibilities of entrance into the new markets and also rather cheap and qualified labour force, has positively influenced economic environment of all Baltic Sea region countries. For the Baltic economies in transition, the regional co-operation has created conditions that support their rapid economic restructuring, development of infrastructure and human capital, and quick rise of competitiveness. To sum up, the Baltic Sea region has good potential for competitive economic development due to its favourable location between East and West and dynamic interdependence between transition and integration, stimulating both processes.
Keywords: 330